2019
DOI: 10.19053/01227238.9970
|View full text |Cite
|
Sign up to set email alerts
|

Experiencia formativa en escuelas monoculturales de la Araucanía, Chile: memoria de mujeres en Cholchol y Maquehue

Abstract: Esta investigación se enmarca en los resultados preliminares de un proyecto Fondecyt regular. Este artículo tiene como objetivo develar descriptivamente la memoria social de cinco mujeres, abuelas indígenas de la comunidades mapuche de Maquehue y del sector Cholchol, con un rango de edad que oscila entre los sesenta y los setenta años, desde sus subjetividades, sus particularidades y sentimientos; el texto aborda el problema de la invisibilización de la sabiduría ancestral indígena de las abuelas mapuche, las … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Since the second part of the 1980s, kindergarten education began to acquire a greater educational value, based on evidence from research in the area, which reported long-term benefits both in the cognitive dimension and socioemotional development, where the professional work of educators is fundamental in the comprehensive development of infants (Huaiquián-Billeke et al, 2016). The literature argues that these benefits, both in the development of cognitive and social skills, must be linked to quality standards to achieve good educational development, since those programs that aim at the care and not the learning of infants tend to have a lower impact on children, showing that training programs and educators are fundamental in the educational processes (Pianta et al, 2009).…”
Section: Scientific Evidence In the Work Of Chilean Early Childhood E...mentioning
confidence: 99%
“…Since the second part of the 1980s, kindergarten education began to acquire a greater educational value, based on evidence from research in the area, which reported long-term benefits both in the cognitive dimension and socioemotional development, where the professional work of educators is fundamental in the comprehensive development of infants (Huaiquián-Billeke et al, 2016). The literature argues that these benefits, both in the development of cognitive and social skills, must be linked to quality standards to achieve good educational development, since those programs that aim at the care and not the learning of infants tend to have a lower impact on children, showing that training programs and educators are fundamental in the educational processes (Pianta et al, 2009).…”
Section: Scientific Evidence In the Work Of Chilean Early Childhood E...mentioning
confidence: 99%
“…Es por esto, que surge la necesidad de articular una base epistemológica del conocimiento escolar que incorpore el conocimiento educativo mapuche, la cual puede constituir un aporte para generar una educación sustentada en el diálogo de saberes, también denominado diálogos interculturales, que son procesos de comunicación entre personas, grupos o comunidades provenientes de diferentes orígenes o culturas. De esta forma, la escuela invade la cultura indígena, alejándose de su esencia, que es vivir en armonía con la naturaleza (Mansilla et al, 2016;Quilaqueo et al, 2016;Huaiquián y Estay, 2019;OPS, 2021). Como sostiene García (2015), para los integrantes de los pueblos indígenas la escuela distancia a los niños de la cultura materna y los inserta en una cultura que les resulta ajena.…”
Section: La Enseñanza De Las Ciencias Desde El Currículum Nacionalunclassified